2007
DOI: 10.1111/j.1746-1049.2007.00042.x
|View full text |Cite
|
Sign up to set email alerts
|

Governance Institutions and Private Investment: An Application to the Middle East and North Africa

Abstract: This paper addresses the issue of the low level of private investment in the Middle East and North Africa (MENA) region, with special emphasis on the role of governance. Based on the existing published reports, we categorize what types of governance institutions are more detrimental to entrepreneurial investments. We then estimate a simultaneous model of private investment and governance quality where economic policies concurrently explain both variables. Our empirical results show that governance plays a sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 77 publications
2
35
0
Order By: Relevance
“…This 5 As we discuss above, we consider that social infrastructure is acting in order to preserve physical capital, decreasing its net depreciation rate. However, we would obtain similar results if we considered a direct and positive effect of social infrastructure on investment.…”
Section: Final Good Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…This 5 As we discuss above, we consider that social infrastructure is acting in order to preserve physical capital, decreasing its net depreciation rate. However, we would obtain similar results if we considered a direct and positive effect of social infrastructure on investment.…”
Section: Final Good Productionmentioning
confidence: 99%
“…However, we go further and consider that the channel is through the protection of physical capital or investment. In fact, empirical literature has found a negative relation between corruption levels and capital accumulation (Campos and Lien, 1999), corruption and productivity (Salinas-Jiménez and Salinas-Jiménez, 2007), social barriers and capital accumulation (Grafton et al, 2007), and social capital and corruption (Bjørnskov, 2003a); it also found a positive relationship between governance institutions and investment (Aysan et al, 2007), responsibility and capital accumulation (Breuer and McDermott, 2009), and trust and capital accumulation (Yamamura and Inyong, 2010). Closer to our work, Bu (2006) presented evidence according to which depreciation rates are higher in developing countries than in developed ones.…”
Section: Introductionmentioning
confidence: 99%
“…'Administrative quality' in the form of control of corruption as well as the investment-friendly profile of administration, law and order is an important influence in decisions about resource commitment (Aysan, Nabli, & Veganzones-Varoudakis, 2007), with strong legal institutions critical in securing property rights and integrity of contract (Haggard, MacIntyre, & Tiede, 2008).…”
Section: Juridical Institutions and Reinvestmentmentioning
confidence: 99%
“…(i) no impacts 1 , negative effects (Ugur & Dasgupta, 2011;Mo, 2001;Mauro, 1995) or positive impacts 2 on investment and economic prosperity; (ii) slight weak impact of corruption on economic growth via the investment channel (Mauro, 1997); (iii) negative effect in specifically investment-oriented lines of inquiry (Everhart et al, 2009;Baliamoune-Lutz & Ndikumana, 2008;Aysan et al, 2007;Brunetti et al, 1998;Mauro, 1997); (iv) perilous effect of foreign investment (Wei, 2000a) and bank credit (Ahlin & Pang, 2008;Wei & Wu, 2001;Wei, 2000b) in studies focused on capital flows; (v) negative return (De la Croix & Delavallade, 2007;Haque & Kneller, 2008) and quality (Tanzi & Davoodi, 1997) of public expenditure, particularly in general (Delavallade, 2006) and military (Gupta et al, 2001) expenditure and (vi) the depletion of governance income (Blackburn et al, 2008;Friedman et al, 2000;Ghura, 1998;Tanzi & Davoodi, 1997).…”
Section: Introductionmentioning
confidence: 99%